The Twenty First Board of Trustees Meeting Institute Sultan Iskandar, June 23, 1997, Bangunan KUWASA Jalan Raja Laut Kuala Lumpur - Board of Trustees Meeting Institute Sultan Iskandar (21st : 1997 : Kuala Lumpur); Universiti Teknologi Malaysia. Institut Sultan Iskandar (Kuala Lumpur : Institute Sultan Iskandar, 1997)
44